A Longitudinal Study of Relationships between Identity Continuity and Anxiety Following Brain Injury - Walsh, R. S.; Muldoon, Orla T.; Fortune, Donal G.; Gallagher, Stephen (Frontiers in Psychology, 2017)
Objective: Anxiety is of particular importance following acquired brain injury (ABI), because anxiety has been identified as a significant predictor of functional outcomes. Continuity of self has been linked to post ABI adjustment and research has linked self-discrepancy to anxiety. This longitudinal study investigates the impact of affiliative and ‘self as doer’ self-categorisationson anxiety. Method: Data was collected at two time points. Fifty-three adult ABI survivors participating in post-acute community neuro-rehabilitation participated at time one and 32 of these participated at time two. Participants completed a 28-item identity questionnaire based on Leach et al.’s (2008) multicomponent model of ingroup identification which measured the strength of affiliative and self as doer identities. Anxiety was measured using the Hospital Anxiety and Depression Scale. Results: Analysis indicates a significant mediated relationship between affiliative identification and anxiety via self as doer identification. Contrary to initial prediction, this relationship was significant for those with consistency in affiliative self-categorisation and inconsistency in ‘self as doer’ self-categorisation. Conclusions: These findings can be interpreted as evidencing the importance of identity continuity and multiplicity following ABI and contribute to the understanding of these through the use of a social identity approach. Key Words: Brain Injury; Social Identity; Self Categorisation; Identity Continuity; Anxiety.